Nitric oxide synthase promotes distension-induced tracheal venular leukocyte adherence. - Aigul Moldobaeva (PLoS ONE, 2014)
The process of leukocyte recruitment to the airways in real time has not been extensively studied, yet airway inflammation persists as a major contributor to lung pathology. We showed previously in vivo, that neutrophils are recruited acutely to the large airways after periods of airway distension imposed by the application of positive end-expiratory pressure (PEEP). Given extensive literature implicating products of nitric oxide synthase (NOS) in lung injury after ventilatory over-distension, we questioned whether similar mechanisms exist in airway post-capillary venules. Yet, endothelial nitric oxide has been shown to be largely anti-inflammatory in other systemic venules. Using intravital microscopy to visualize post-capillary tracheal venules in anesthetized, ventilated mice, the number of adherent leukocytes was significantly decreased in eNOS-/- mice under baseline conditions (2±1 cell/60 min observation) vs wild type (WT) C57BL/6 mice (7±2 cells). After exposure to PEEP (8 cmH2O for 1 min; 5 times), adherent cells increased significantly (29±5 cells) in WT mice while eNOS-/- mice demonstrated a significantly decreased number of adherent cells (11±4 cells) after PEEP. A similar response was seen when thrombin was used as the pro-inflammatory stimulus. In addition, mouse tracheal venular endothelial cells studied in vitro after exposure to cyclic stretch (18% elongation) or thrombin both demonstrated increased p-selectin expression that was significantly attenuated by NG-nitro-L-arginine methyl ester, N-acetylcysteine amide (NACA) and excess BH4. In vivo treatment with the ROS inhibitor NACA or co-factor BH4 abolished completely the PEEP-induced leukocyte adherence. These results suggest that pro-inflammatory stimuli cause leukocyte recruitment to tracheal endothelium in part due to eNOS uncoupling.